APLICAÇÕES MÓVEIS À BEIRA DO LEITO - Jesus, Cayo Pabllo Santana de (2009)
Several efforts have been attempt in developing mobile application for the healthcare domain. Several of these applications, however, have not met the requirements imposed by the inherent mobile nature of medical activities and limitations of the mobile devices. In this scene, this work aims at identify two major demands for mobile computing applications involving both nurses and doctors working at hospital environments. The first demand refers to the process of medication administration. This process, performed by nurses, is considered one of the most critical activities at a hospital, because the occurrence of any failure has a serious impact on patient health. The second demand deals with the presentation of information concerning patients´ records. Doctors spend most of their time checking, analyzing and monitoring clinical status of patients. In order to meet these demands, this work presents two mobile applications: the Digital Assistant for Medication Administration (DAMA) and the Medical Digital Assistant (MDA). The DAMA aims at assisting nurses during the medication administration process, providing information in real time at the point of care, identifying all the actors involved in the process and minimizing occurrences of errors. The MDA goal is to assist physicians in carrying out its activities at any time, even when they are moving among various hospitals spots.